Stress and well-being within Fife Fire Service - Blackburn, Pennie (The University of Edinburgh, 1998)
Emergency Services Personnel are exposed to critical incidents at a far higher rate than the general population. Therefore, there may be a greater risk to people in critical occupations of developing post traumatic stress symptomatology. The aim of the study was to consider the level of stress and well-being reported in a sample of Fire Fighters. A questionnaire survey of the Fife Fire And Rescue Service was carried out which explored the relationship between demographic variables, the severity of exposure to an identified incident, on~scene and post event coping strategies and outcome measures of general health, well-being, and post traumatic stress disorder. Interviews of a small sub-sample were also conducted which provided more qualitative data concerned with aspects of work related stress. The results are discussed in the context of the current literature. Implications for the prevention of stress in Emergency Service Personnel are also considered.